John Henry Williams, 1747-1829: "political clergyman" : war, the French Revolution, and the Church of England - Haydon, Colin (Boydell & Brewer, 2007)
First full-length study of the life and career of John Henry Williams, one of the most fascinating figures of the eighteenth-century church. John Henry Williams was the vicar of Wellesbourne in south Warwickshire from 1778 until his death some fifty years later. A dedicated pastor, displaying an 'enlightened and liberal' outlook, his career illuminates the Church of England's condition in the period, and also a clergyman's place in local society. However, he was not merely a country parson. A `political clergyman', Williams engaged fervently in both provincial and national political debate, denouncing the war with revolutionary France between 1793 and 1802, and published a series of forceful sermons condemning the struggle on Christian principles. To opponents, he appeared insidious and blinkered, but to admirers he was 'a sound divine, and not a less sound politician'. This book, the first to examine Williams' career in full, is a detailed, vivid, and sometimes moving, study of a man who occupies an honorable and significant position in the Church of England's history and in the history of British peace campaigning. Dr COLIN HAYDON teaches in the Department of History at the University of Winchester.